2020
DOI: 10.1016/j.pharmthera.2020.107618
|View full text |Cite
|
Sign up to set email alerts
|

Glycyrrhizin: An alternative drug for the treatment of COVID-19 infection and the associated respiratory syndrome?

Abstract: Safe and efficient drugs to combat the current COVID-19 pandemic are urgently needed. In this context, we have analyzed the anti-coronavirus potential of the natural product glycyrrhizic acid (GLR), a drug used to treat liver diseases (including viral hepatitis) and specific cutaneous inflammation (such as atopic dermatitis) in some countries. The properties of GLR and its primary active metabolite glycyrrhetinic acid are presented and discussed. GLR has shown activities against different viruses, including SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
221
0
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 252 publications
(228 citation statements)
references
References 224 publications
(195 reference statements)
0
221
0
7
Order By: Relevance
“…Glycyrrhizin (also called glycyrrhizic acid), a triterpenoid saponin isolated, is used in Chinese Pharmacopeia (54). Recently, it has been demonstrated that this triterpene may be a hope in the Covid-19 pandemic (55). Diterpenes are often with the molecular formula C 20 H 32 , which is composed of repeated isoprene subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizin (also called glycyrrhizic acid), a triterpenoid saponin isolated, is used in Chinese Pharmacopeia (54). Recently, it has been demonstrated that this triterpene may be a hope in the Covid-19 pandemic (55). Diterpenes are often with the molecular formula C 20 H 32 , which is composed of repeated isoprene subunits.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizinic acid (GLR), a triterpenoid saponin, is mainly isolated from licorice root, which is effective against a variety of human viruses ( Ashfaq et al, 2011 ). The study by the researcher ( Bailly and Vergoten, 2020 ) shows clear evidence that glycyrrhizinic acid isolated from licorice has antiviral properties that can deactivate the virus and stop replication. Droplet microbes are locked on the agent and infectious droplets are rapidly opened by hydrophilic action leading to exposure of viruses.…”
Section: Resultsmentioning
confidence: 99%
“…Altered lipid profiles have been associated with poor outcome of multiple sclerosis (MS) (75)(76)(77)(78)(79)(80), an autoimmune disease characterized by inflammatory cell infiltrates and demyelination (81,82). In this regard, obesity, among other environmental factors, has been described as a risk factor for MS in several epidemiological studies (83)(84)(85)(86). In animal models of experimental autoimmune encephalomyelitis (EAE), the most common experimental model for human inflammatory demyelinating disease, selected agonists of LXRs (e.g., T0901317) have been shown to improve the severity of central nervous system inflammation (30).…”
Section: Lxrs and Autoimmunitymentioning
confidence: 99%